2019
DOI: 10.11604/pamj.2019.34.18.18917
|View full text |Cite
|
Sign up to set email alerts
|

Aspects diagnostiques, thérapeutiques et pronostiques du diabète gestationnel au Centre Hospitalier Universitaire Sylvanus Olympio

Abstract: IntroductionLes objectifs de cette étude étaient de décrire les aspects diagnostiques, pronostiques et thérapeutiques du diabète gestationnel au CHU Sylvanus Olympio de Lomé.MéthodesIl s'est agi d'une étude descriptive transversale réalisée sur 5 ans allant du 1er janvier 2013 au 31 décembre 2017. Elle a concerné 125 gestantes ayant accouché, suivies en médecine interne et dans le Service de Gynéco-obstétrique.RésultatsLa moyenne d'âge maternelle était de 30,84±4,17 ans. Les facteurs de risque les plus rencont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(9 citation statements)
references
References 7 publications
2
5
2
Order By: Relevance
“…The observation that pregnant women with GDM tended to be younger is in line with the observation of Orru MI et al who, speaking of gestational pre-diabetes, had observed that relatively younger pregnant women were also affected and this should not exclude them from screening for GDM [2]. The age level of the pregnant women in this study is comparable to that done by Kodjo Agbeko and by Leye A. who respectively observed mean ages of 30.84 ± 4.17 years [16] and 29.8 ± 6.2 years [9]. The observation on this level of young age differs from those of most authors such as Tandu-Umba in Kinshasa [14], Tieu J [17] and Diane Farrar [4], who had observed that advanced age was a risk factor for eligibility for selective GDM screening.…”
Section: Discussionsupporting
confidence: 91%
“…The observation that pregnant women with GDM tended to be younger is in line with the observation of Orru MI et al who, speaking of gestational pre-diabetes, had observed that relatively younger pregnant women were also affected and this should not exclude them from screening for GDM [2]. The age level of the pregnant women in this study is comparable to that done by Kodjo Agbeko and by Leye A. who respectively observed mean ages of 30.84 ± 4.17 years [16] and 29.8 ± 6.2 years [9]. The observation on this level of young age differs from those of most authors such as Tandu-Umba in Kinshasa [14], Tieu J [17] and Diane Farrar [4], who had observed that advanced age was a risk factor for eligibility for selective GDM screening.…”
Section: Discussionsupporting
confidence: 91%
“…Among 25 women with GDM, 12 (48%) had a history of miscarriages and 4 (16%) had gone through preterm birth. Similar results have been reported by Djagadou et al [35], who showed that women with gestational diabetes had more frequently a history of spontaneous miscarriages and premature birth compared to control women. In the present study, most of those diagnosed with gestational diabetes were aged between 30 and 40 years.…”
Section: Discussionsupporting
confidence: 90%
“…Consequently, two experimental groups of subjects were then established: a group of women positive for GDM and a group of women negative for GDM considered as the control group. Then, twenty-five (25) women with GDM and thirty-five (35) age-matched and body mass index-matched pregnant controls were selected and submitted for blood collection and biochemical and immunological assays.…”
Section: Screening Of Gestational Diabetes Mellitusmentioning
confidence: 99%
“…There is a positive, linear correlation with no real threshold between the risk of pregnancy complications and maternal blood glucose, raising the problem of diagnostic criteria for GDM [3] . Regardless of the type of GDM, it is a metabolic and obstetrical emergency [4] . GDM results in hyperglycemia of varying severity and can be the cause of maternal and/or fetal complications (pre-eclampsia, cesarean section, macrosomia) warranting optimal multidisciplinary management [2,4,5] .…”
Section: Introductionmentioning
confidence: 99%
“…Regardless of the type of GDM, it is a metabolic and obstetrical emergency [4] . GDM results in hyperglycemia of varying severity and can be the cause of maternal and/or fetal complications (pre-eclampsia, cesarean section, macrosomia) warranting optimal multidisciplinary management [2,4,5] . It is recognized that GDM increases the risk of preeclampsia and cesarean section in the absence of treatment [3] .…”
Section: Introductionmentioning
confidence: 99%